Help-seeking process among perpetrators and co-victims of filicide - Léveillée, Suzanne (Journal of family violence, 2023)
The present research focuses on help-seeking process among perpetrators and co-victims of filicides committed in the province of Quebec. This study draws a portrait of help-seeking behaviors among perpetrators and co-victims of a filicide and presents two clinical vignettes to illustrate the help-seeking process. The 28 cases of filicides (14 paternal and 14 maternal filicides) committed in Quebec between 2007 and 2012 were analyzed using the Grille d’analyse multidimensionnelle de l’homicide intrafamilial. One-third of filicide perpetrators consulted a professional or a support service in their lifetime. The requests for assistance tend to decrease in the year prior to the homicide. A small percentage of requests for help are observed among co-victims of filicide. The results allow to describe a complete portrait of help-seeking from perpetrators and co-victims of filicide and help raise the importance of understanding the phenomenon with a robust and responsive theoretical framework. This study highlights the relevance of developing and maintaining specific services for men and women in crisis and at risk of violent behavior. Informing and raising the awareness of the population as well as the professionals working with this clientele could be one more step towards better prevention.